Opportunity or necessity? Youth agripreneurs in Benin, Ethiopia and Senegal - Zaneta Kubik; Tigabu Degu Getahun; Patrice Ygué Adegbola; Assane Beye; Ahmadou Aly Mbaye (University of Bonn, Center for Development Research (ZEF), 2024)
This report provides a descriptive analysis of youth entrepreneurs in agribusiness in Sub-Saharan Africa. Based on primary data collected in Benin, Ethiopia and Senegal, it offers insights into the socio demographic background of the youth entrepreneurs as well as a detailed account of the business units they run. The analysis shows a diversity of business activities across the entire food value chain, but with a strong concentration in farming, followed by processing and retail. Pluri-activity, which typically escapes standard sectoral classifications, is very present across the sample and an important share of agripreneurs are involved in a mix of activities, combining farming with processing or retail, and parallel commercialization of food products with and without transformation. The businesses are micro to small in size, with on average three paid employees, excluding the owner, but nevertheless offer a non-negligible employment creation potential at the aggregate level. In total, the 634 sampled agripreneurs create more than 2,500 jobs. Despite their small scale, these businesses report a robust turnover with, however, wide variation, especially at the higher end of the distribution. On the other hand, due to the cross-sectional nature of the data, it is impossible to assess the growth potential of these businesses. However, considering the (mainly financial) constraints that the owners report both at the start-up as well as for already existing businesses, it appears that youth entrepreneurs struggle to overcome initial challenges. Roughly half of the agripreneurs are opportunity-driven, meaning that they voluntarily choose to start a business as a response to perceived business opportunities. This result suggests that, contrary to popular perceptions, agribusiness continues to play an important role in youth aspirations. The start up motivations are likely to influence the performance of the businesses. Opportunity-driven agripreneurs score better on a number of indicators, including turnover, job creation, innovation adoption, and self-reported overall business performance. This may have important policy implications, in that opportunity-driven agripreneurs would require different policy support than necessity-driven agripreneurs.
Keywords: M20; O13; O15; O17; O31; 330; youth; agripreneur; agriculture; employment; aspirations; business; Africa